PROBLEMATICS OF THE IMPLEMENTATION OF THE PRESIDENTIAL THRESHOLD IN ELECTIONS - Fadhlan Fahmi Tarigan; Fiyan Hamdi Lubis; Abdul Hadi Musthofa (NOMOI Law Review, 2023)
Problems regarding the application of the Presidential Threshold in elections are always in the spotlight when elections are approaching. But even so, there are still many ordinary people who do not understand or even do not know what the Presidential Threshold is. The purpose of this research is for readers to know and understand what the presidential Threshold is. traces and history of the application of the Presidential Threshold, and what is the controversy over the application of the presidential threshold. The research method used is Normative Juridical, namely legal research with a literary approach based on related references which aims to see what is meant by the presidential threshold and how it is regulated within the law. The data used in this study is secondary data, namely data from previous research to become a reliable reference source. The topic of discussion in this study is to discuss the meaning of the presidential threshold, how the historical development of the presidential threshold in Indonesia from the beginning was apply to date, and the controversy over the implementation of the presidential threshold in Indonesia.